MODEL PENDIDIKAN AGAMA ISLAM INTEGRASI-INTERKONEKSI (HIKMAH dan WISDOM SEBAGAI VISI PENDIDIKAN MASA) - Boli, Mukdar; Tobroni, Tobroni; Fariadi, Fariadi (Ibtida'iy : Jurnal Prodi PGMI, 2024)
The integrated-interconnected Islamic Religious Education Model is needed so that there is no dichotomy of religious knowledge and general knowledge. because all scientific aspects require other scientific aspects to perfect each other. In order to understand each other, the various PAI models are therefore interrelated and complementary solutions. The integration-interconnection model of Islamic religious education will be successful if it is carried out with knowledge, experience and practice of Islamic values and accompanied by work intelligently, thoroughly and sincerely. This article begins with a thematic approach to the word "hikmah" in the Koran. The historical thematic approach stems from explaining verse by verse. In this way, the essence of the word wisdom can be obtained with a meaning that can be induced, so the main tool used is the encyclopedia or dictionary al-Mu'jam al-Mufahras li alfadhil Qur'an and Fathu al-Rahman. The basic theory used is the Ruhiyah theory developed by Ikhwanushafa (961-986 h.260-261) and the theory of "The Hearts' Code" by Paul Pearsell in 1999, as the result of research on the human heart, liver and spirit for many years. year in the United States. Several prominent views regarding wisdom as a vision of future education were also discussed supervisedly. It is concluded that education with a wisdom and wisdom approach is a modern vision of a model for educational institutions in the future where reason and feeling can unite.